Stable structure and optical properties of fused silica with NBOHC-E＇ defect - 芦鹏飞 伍力源 杨阳 王唯正 张春芳 杨创华 苏锐 陈军 (Chinese physics B, 2016)
First-principles method is used to simulate the stable structure and optical properties of a 96-atom fused silica.The preferable structure of NBOHC-E＇（non-bridging oxygen hole center（NBOHC） and E＇ center） pair defect is predicted to be located at 2.4 A^° for the Si-O bond length.The quasi-particle GOWO calculations are performed and an accurate band gap is obtained in order to calculate the optical absorption properties.With the stretching of the Sil-O1 bond,an obvious redshift can be observed in the absorption spectrum.In the case of NBOHC-E＇ pair,the p-orbital DOS of Si1 atom will shift to the conduction band.Two obvious absorption peaks can be observed in the absorption spectrum.The calculation reproduced the peak positions of the well-known optical absorption bands.